Constructing Conductive Network in Hybrid Perovskite for a Highly Efficient Microwave Absorption System. (19th July 2022) - Zhang, Zhi; Xiong, Ziming; Yao, Yao; Wang, Derong; Yang, Zhiqian; Zhang, Pin; Zhao, Qing; Zhou, Wenke
Abstract: Electronic devices have brought huge convenience to daily lives; however, a large amount of electromagnetic radiation pollution is generated. Therefore, an urgent demand for electromagnetic wave absorbing materials featuring "low thickness, wide frequency band and strong absorption" is put forward. Here, a strategy of introducing a conductive carbon nanotubes (CNTs) network into CH3 NH3 PbI3 (MAPbI3 ) is developed to construct an electromagnetic wave absorbing system. As the absorption center, MAPbI3 dominates the absorption band via an electric polarization process. Meanwhile, the CNTs construct an efficient conductive network, which supply a transmission path for free electrons inside the MAPbI3 crystals and enhance conduction loss. In comparison with the insulated network formed by MoO3 /MAPbI3, it is speculated that the broadened absorption bandwidth and reduced absorption thickness originate from the conductive network of CNTs. As a result, when the CNTs is 7.7% (mass ratio), the reflection loss strength of MAPbI3 /CNTs reaches −57.71 dB at 13.96 GHz and the corresponding effective absorption bandwidth is 6.32 GHz (11.68–18.00 GHz), with an absorber thickness of 1.96 mm. The method of constructing conductive network proves a great potential of hybrid perovskite in the field of electromagnetic wave absorption and provides feasible strategies for the absorption regulation of dielectric loss‐type materials. Abstract : Carbon nanotubes (CNTs) are used to construct a highly efficient conductive network in MAPbI3 crystals, which supply a transmission path for free‐electron and enhance the conduction loss for the electromagnetic wave. The champion effective absorption bandwidth is promoted to 6.32 GHz with a thickness of 1.96 mm. This work proves the great potential of hybrid perovskite in the field of dielectric‐loss‐dominated wave absorption.